Analisis Pelaksanaan Alih Media Rekam Medis Manual ke Elektronik di Pelayanan Rawat Inap RS Bhakti Mulia - Mawardi, Arilla Nugrahi; Sonia, Dina Sonia; Widjaja, Lily Widjaja; Rumana, Nanda Aula Rumana (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2025)
The transition from manual medical records to electronic medical records (EMR) is a strategic policy of the Indonesian Ministry of Health through Ministerial Regulation No. 24 of 2022, which requires all healthcare facilities to implement digital recording. This study aims to investigate the implementation of the transition from physical documents to an electronic system in the inpatient unit at Bhakti Mulia Hospital. The research method used is qualitative descriptive, with data collection techniques including observation and interviews with six informants from the medical records unit. The research findings indicate that the hospital has established Standard Operating Procedures (SOPs) for the transition to electronic medical records, as well as retention policies for inactive documents, in accordance with national regulations. The transition process has been ongoing since 2022, supported by infrastructure such as scanners, computers, and the SIMRS application. Supporting factors are evaluated using the 5M management approach (People, Budget, Methods, Equipment, and Materials). As a result, implementation has not been optimal due to limitations in human resources, technical constraints with equipment, communication challenges, and human errors in the completeness of medical record documentation. It is recommended to increase the number and quality of human resources according to qualifications, provide further training, conduct regular system evaluations, and align communication between units. Therefore, support from management and regular evaluations are needed to ensure that the media transfer process can run optimally.